The development and content of movement quality assessments in athletic populations: A systematic review and multilevel meta-analysis - Wijekulasuriya, G. A.; Woods, C. T.; Kittel, A.; Larkin, P. (Sports Medicine - Open, 2025)
Background Despite their prominence in the sport and human movement sciences, to date, there is no systematic insight about the development and content of movement quality assessments in athletic populations. This is an important gap to address, as it could yield both practical and scientific implications related to the continued screening of movement quality in athletic contexts. Hence, this study aimed to systematically review the (i) developmental approach, (ii) movements included, (iii) scoring system utilised, and (iv) the reliability of movement competency assessments used in athletic populations.